2‐(Alkylamino)‐3‐aryl‐6, 7‐dihydrobenzofuran‐4(5H)‐ones: Improved Synthesis and their Photophysical Properties. Issue 5 (2nd July 2015) - Kumar, Manoj; Kumawat, Lokesh Kumar; Gupta, Vinod Kumar; Sharma, Anuj
Abstract Furans are an important class of compounds and exhibit a diverse range of activities and properties. As such, improved synthetic access to furans is an important research goal. In the present report, a solvent‐ and catalyst‐free reaction between 5, 5‐dimethyl‐1, 3‐cyclohexanedione (dimedone), an aryl aldehyde and an isocyanide under microwave irradiation is presented. This method is significantly improved from previously described protocols in terms of applicability of wide ranging aryl aldehydes, better yields, shorter reaction times, facile work up and essentially no need of column chromatography. The photophysical properties of this series of compounds were studied for their possible applicability in the field of metal ion sensors. In solution, two compounds, 2‐(cyclohexylamino)‐3‐(1H‐indol‐3‐yl)‐6, 6‐dimethyl‐6, 7‐dihydrobenzofuran‐4(5H)‐one (1 i) and 2‐(tert‐butylamino)‐3‐(1H‐indol‐3‐yl)‐6, 6‐dimethyl‐6, 7‐dihydrobenzofuran‐4(5H)‐one (1 j), underwent an observable color change from yellow to colorless in the presence of aluminum(III) ions. Further studies to investigate the UV absorption and luminescence behavior of these compounds revealed their utility as "naked‐eye sensors" for aluminum detection.